Quality of Service for Health Workers at the Motaha Community Health Center, South Konawe Regency Southeast Sulawesi - Idris, Idris; Nurhaedah, Nurhaedah; Rosdiana, Rosdiana; Anurogo, Dito; Sipahutar, Pongki (International Journal of Health Sciences, 2024)
A community health center (puskesmas) is a functional organization that carries out health efforts that are comprehensive, integrated, equitable, acceptable and affordable to the community and use the results of appropriate science and technology development, at a cost that can be borne by the government and the community. The aim of this research is to determine the quality of service of health workers at the Motaha District Health Center. South Konawe, Southeast Sulawesi. This type of research is descriptive observational. This type of research is observational, descriptive in nature, which aims to describe the quality of service of health workers at the Motaha District Health Center. South Konawe, Southeast Sulawesi. Based on the results of field research, it shows that 40 respondents (76.9 %) had sufficient knowledge and 12 respondents (23.1%) had insufficient knowledge.